In-service teachers’ interpretative repertoires about language: The teacher promotion examination context - Werbińska, Dorota (Neofilolog, 2023)
While studies on interpretative repertoires have been conducted in SLA, this is still a fairly new topic with regard to language teachers. Due to various contextual differences, teachers’ interpretative repertoires change, which also seems a sufficient reason why they should be investigated on a regular basis. The aim of this study is to identify and analyse Polish in-service teachers’ (n=48) interpretative repertoires concerning language which emerged in the teachers’ discourses in the context of their taking a promotion examination. Acknowledging the complexity of this issue, interpretative repertoires, including the SLA studies devoted to identifying them, are first discussed, followed by a description of the study. In terms of methodology, the author’s field notes for data collection were used. The data were coded following the content analysis approach, and 6 conceptualizations of language emerged: language as system, language as communication, language as culture, but also as translanguaging, as preparation for exam, and as life preparation. The findings can be used to adopt new directions in future research on Polish teachers’ language-based interpretative repertoires. The study may also provide information for school policies and practice.